Sedap Ramyeon / Aishah Amira Ahmad Khalil - Ahmad Khalil, Aishah Amira (2020)
A marketing plan report on Sedap Ramyeon brand is presenting to do an analysis towards the market and market testing on new product line that going to introduce to consumers. Sedap Ramyeon is selling instant ramen as their main products in the company, however the company has to do more strategies in order to go for global market. Therefore, some analysis and implementations have been done for the blueprint in the future year. Environmental analysis on company and the country shows out who is company target market is and how each of the forces can affect company operations as well as the buying patterns of consumers. Moreover, SWOT analysis also been drew out to enhance the strength that company has and also to find initiatives to improve company’s weakness. Objectives of company listed out as the goals for company to achieve. Thus, through the objectives we can know it very well what is our aim and how we achieve these objectives by following year. Lastly, it is the evaluation and control on budget that we going to use. In order to control the over use of cost, a budget table will going to show the market activities with some brief description as well as the calculations on it.